2012
DOI: 10.1016/j.ntt.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

d-Methionine protects against cisplatin-induced neurotoxicity in cortical networks

Abstract: Cisplatin is a platinum-based chemotherapeutic agent widely used for the treatment of various types of cancer. Patients undergoing cisplatin treatment often suffer from a condition known as "chemobrain", ototoxicity, peripheral neuropathy, weight loss, nausea, vomiting, nephrotoxicity, seizures, hearing loss and tinnitus.D-Methionine (D-Met), a sulfur-containing nucleophilic antioxidant, has been shown to prevent cisplatininduced side effects in animals without antitumor interference. In this study, we have us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Oxidative stress may be the most important mechanism among these mechanisms that are proposed to explain neurotoxicity, and in this regard, targeting oxidative stress can limit cisplatininduced neurotoxicity while preserving anticancer efficacy. Therefore, several antioxidant molecules such as coenzyme Q10 (da Silva , walnut (Shabani et al, 2012b), D-Methionine (Gopal et al, 2012), alpha lipoic acid (Tuncer et al, 2010), melatonin (Tuncer et al, 2010), and curcumin (Al Moundhri et al, 2013;Mendonca et al, 2013) have been used to in an effort to either mitigate or prevent cisplatin-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress may be the most important mechanism among these mechanisms that are proposed to explain neurotoxicity, and in this regard, targeting oxidative stress can limit cisplatininduced neurotoxicity while preserving anticancer efficacy. Therefore, several antioxidant molecules such as coenzyme Q10 (da Silva , walnut (Shabani et al, 2012b), D-Methionine (Gopal et al, 2012), alpha lipoic acid (Tuncer et al, 2010), melatonin (Tuncer et al, 2010), and curcumin (Al Moundhri et al, 2013;Mendonca et al, 2013) have been used to in an effort to either mitigate or prevent cisplatin-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of excitotoxicity, the disturbance of membrane ionic balance that leads to degeneration-such as that induced by excess glutamate in Huntington Disease symptoms or methamphetamine-activated dopamine surge (Virmani et al 2003;Vamos et al 2010)-may be more relevant in the discussion of the protective action of L-carnitine within the framework of the inhibitory neurotransmitter system. Likewise, we suspect that perhaps the protective mechanism of D-methionine against platinum toxicity observed in our previous study (Gopal et al 2012) may partly be a counteracting measure against excitotoxicity by GABAergic inhibition.…”
Section: Discussionmentioning
confidence: 74%
“…Our previous studies were among the first to adapt functional studies of neuronal networks for testing the protective properties of L-carnitine and D-methionine (Wu et al 2011;Gopal et al 2012). We observed that both compounds elicited consistent inhibitory responses in neuronal networks.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations